Interaction between Chinese medicine and digoxin: Clinical and research update - Zhuang, Wei; He, Tao; Jia, Bei-Bei; Wang, Zhi-Zhou; Zhang, Lan; Dong, Xian-Zhe; Xi, Sheng-Yan (Frontiers in Pharmacology, 2023)
Background: Digoxin is one of the most widely and commonly used cardiac drug, which plays an irreplaceable role in treating heart failure and arrhythmia. The 2010 Edition of Pharmacopoeia of the People’s Republic of China stipulates that the effective range of digoxin plasma concentration is 0.5–2.0 ng/mL and it is toxic at plasma concentration >2 ng/mL. Its effective plasma drug concentration is close to the toxic concentration, and large individual differences in the effects of the drug have been observed. It is often used in combination with other drugs, but drug interactions have a great impact on the plasma concentration of digoxin and lead to adverse reactions (ADRs), such as poisoning. Most of the reported drug interactions are with Western drugs. However, there are many combinations of traditional Chinese medicine (TCM) and Western drugs, TCM interacting with digoxin comprises monomer components, single medicines, and Chinese patent medicines. Aim of the study: We aimed i) to provide an overview of the TCM formulations affecting the pharmacology of digoxin and their mechanisms of action and ii) to provide a theoretical reference for the safe and rational use of digoxin in combination with TCM in clinical practice and to avoid ADRs. Methods: A literature search of electronic databases, including PubMed, MEDLINE, Cochrane Library, Web of Science, China National Knowledge Infrastructure, and WANFANG Data, was performed to search for articles published between 1 January 1960, and 1 August 2022. Search terms used included “digoxin,” “traditional Chinese medicine,” “Chinese patent medicine,” and “adverse reactions” and their combinations. Results: A total of 49 articles were obtained, including clinical reports, pharmacological experiments and in vitro experiments. The mechanisms of action affecting the pharmacology of digoxin are complex. TCM formulations may affect the pharmacology of digoxin in vivo by influencing gastrointestinal motility or gastric juice pH, regulating P-glycoprotein levels, exerting cumulative pharmacological effects, and enhancing the sensitivity of the heart to digoxin. Although studies have shown that some TCM formulations interact with digoxin, they may be influenced by the complexity of the composition and the pharmacological effects of the TCM, the sensitivity of digoxin concentration determination methods, etc. The results of existing studies are controversial and further in-depth studies are required. Conclusion: Combinations of digoxin and TCM formulations are commonly used. This article serves as a reference to understand the interactions between TCM formulations and digoxin to avoid the occurrence of ADRs and improve the efficacy and safety of digoxin.